Efficacy and safety of transcranial direct current stimulation over the left dorsolateral prefrontal cortex in children and adolescents with attention-deficit/hyperactivity disorder: a randomized, triple-blinded, sham-controlled, crossover trial - Guimarães, Rachel Silvany Quadros; Bandeira, Igor D.; Barretto, Bianca Lima; Wanke, Thamires; Alves, Clara Oliveira Carvalho; Barretto, Thiago Lima; Carvalho, Chrissie Ferreira de; Dorea-Bandeira, Ingrid; Tolentino, Arthur; Lins-Silva, Daniel H.; Lucena, Pedro H.; Lucena, Rita (Frontiers in Psychiatry, 2024)
Although pharmacological treatment for Attention-Deficit/Hyperactivity Disorder (ADHD) has demonstrated efficacy, several individuals persist in experiencing social and academic impairment. Additionally, the occurrence of significant side effects may render the use of psychotropic medications untenable. However, Transcranial Direct Current Stimulation (tDCS), a non-invasive brain stimulation technique, shows promising results in treating ADHD. Objectives: To investigate the efficacy and safety of tDCS on the performance of children and adolescents with ADHD in neuropsychological tests involving visual attention, visual and verbal working memory, and inhibitory control. Methodology: This study was a triple-blind, randomized, sham-controlled, crossover clinical trial. The intervention consisted of a daily session of tDCS (2mA) or sham targeting the left dorsolateral prefrontal cortex (L-DLPFC), for 30 minutes, on five consecutive days. The primary outcome was change in the Visual Attention Test, Fourth Edition (TAVIS-4) before and after each intervention. Subjects were also evaluated pre and post-tDCS using the Digit Span subtest of the Wechsler Intelligence Scale for Children, Fifth Edition (WISC-V), the Developmental Neuropsychological Assessment, Second Edition (NEPSY-II) Inhibiting Response (IR) subtest, and the Corsi Block-Tapping Task. Results: 15 individuals were included, and no statistically significant difference was observed when comparing the results of the TAVIS-4, the IR of NEPSY-II, and the intragroup Digit Span subtest of WISC-V undertaken before and after the procedure. Adverse events were mainly self-limiting and transient. The participants did not perceive any benefit from tDCS when measured on the Patient Global Impression of Improvement (PGI-I) Scale. Conclusion: This study did not meet its primary endpoint and found no performance enhancement in any investigated neuropsychological outcomes relating to the intervention group.